Computer Science and Software Engineering - Dr. Ritu Sindhu2, Meenakshi Dhamija1 , (International Journal of Scientific Research and Management (IJSRM), 2016)
Network Security is the most vital component in information security because it is responsible for securing allinformation passed through networked computers. Network Security refers to all hardware and software functions,characteristics, features, operational procedures, accountability, measures, access control, and administrative andmanagement policy required to provide an acceptable level of protection for Hardware and Software , and information in anetwork. Only one particular element underlies many of the security mechanisms in use: Cryptographic techniques; henceour focus is on this area Cryptography. Cryptography is an emerging technology, which is important for network security.Research on cryptography is still in its developing stages and a considerable research effort is still required for securedcommunication